The Dynamics of Local Government and Governance Studies: A Bibliometric Analysis of Scopus Publications (2017–2025) - Itno Husen; Rahmat Abd Fatah (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study aims to analyze the evolving dynamics of local government and governance research through a bibliometric approach based on Scopus data from 2017 to 2025. Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, the study integrates network analysis using VOSviewer on 612 selected articles from an initial dataset of 5,744 documents. The findings reveal a significant increase in publication output alongside the emergence of three principal research clusters: participatory governance, model-based empirical approaches, and technology-driven governance. These patterns indicate a paradigm shift from normative frameworks toward evidence-based and digital governance. Furthermore, the analysis uncovers notable geographical disparities in knowledge production, with a concentration of scholarly contributions in specific countries dominating the global discourse. This study contributes theoretically by synthesizing multiple governance paradigms into an integrated analytical framework, while offering practical insights through a comprehensive mapping of research developments. Consequently, it provides a critical foundation for understanding the trajectory of local governance in an increasingly dynamic and complex global context.